Influence of mandibular and palatal intraoral appliances on erosion in situ study outcome - Maisa Camillo Jordão; Franciny Querobim Ionta; Bianca Tozi Portaluppe Bergantin; Fernanda Lyrio Mendonça; Natália Mello dos Santos; Heitor Marques Honório; Thais Marchini de Oliveira; Daniela Rios (University of São Paulo, 2019)
Abstract The standardization of in situ protocols for dental erosion is important to enable comparison between studies. Objective: Thus, the objectives of this study were to evaluate the influence of the location of in situ intraoral appliance (mandibular X palatal) on the extent of enamel loss induced by erosive challenges and to evaluate the comfort of the appliances. Material and Methods: One hundred and sixty bovine enamel blocks were selected according to their initial surface hardness and randomly divided into two groups: GI - palatal appliance and GII - mandibular appliance. Twenty volunteers wore simultaneously one palatal appliance (containing 4 enamel blocks) and two mandibular appliances (each one containing 2 enamel blocks). Four times per day during 5 days, the volunteers immersed their appliances in 0.01 M hydrochloric acid for 2 minutes, washed and reinserted them into the oral cavity for 2 hours until the next erosive challenge. After the end of the in situ phase, the volunteers answered a questionnaire regarding the comfort of the appliances. The loss of tissue in the enamel blocks was determined profilometrically. Data were statistically analyzed by paired t-test, Chi-square and Fisher's Exact Test (p<0.05). Results: The enamel blocks allocated in palatal appliances (GI) presented significantly higher erosive wear when compared to the blocks fixed in mandibular appliances (GII). The volunteers reported more comfort when using the palatal appliance. Conclusions: Therefore, the palatal appliance is more comfortable and resulted in higher enamel loss compared to the mandibular one.